1999
DOI: 10.1159/000029408
|View full text |Cite
|
Sign up to set email alerts
|

German Version of the Epworth Sleepiness Scale

Abstract: Background: The Epworth Sleepiness Scale (ESS) is a questionnaire widely used in English speaking countries for assessment of subjective daytime sleepiness. Objective: Our purpose was to translate and validate the ESS for use in German-speaking countries. Methods: A German translation of the ESS was administered to 159 healthy German-speaking Swiss and to 174 patients with various sleep disorders. Results: The mean ± SD of ESS scores in normals was 5.7 ± 3.0, in patients it was 13.0 ± 5.1 (p < 0.001). Scores w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
175
2
12

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 255 publications
(209 citation statements)
references
References 15 publications
17
175
2
12
Order By: Relevance
“…For the 135 individuals assessed in the present study, the scores obtained on the ESS-BR showed internal consistency similar to that of translations validated elsewhere, (24)(25)(26)(27)(28) despite the cultural and language differences among the populations analyzed. Comparing the ESS-BR scores obtained in the present study with those obtained in studies applying the original ESS, we found the scores to be similar for the control and OSAHS groups.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…For the 135 individuals assessed in the present study, the scores obtained on the ESS-BR showed internal consistency similar to that of translations validated elsewhere, (24)(25)(26)(27)(28) despite the cultural and language differences among the populations analyzed. Comparing the ESS-BR scores obtained in the present study with those obtained in studies applying the original ESS, we found the scores to be similar for the control and OSAHS groups.…”
Section: Discussionsupporting
confidence: 78%
“…(25)(26)(27)(28) In one study, (19) the ESS scores were significantly higher for patients with severe OSAHS than for those with mild or moderate OSAHS (p < 0.001), although no statistically significant difference was found between the mild and moderate forms. Unlike other validation studies, the present study evaluated only individuals submitted to polysomnography, which enhanced the stringency of the selection of the groups.…”
Section: Discussionmentioning
confidence: 92%
“…These questionnaires included, in order, a questionnaire on caffeine consumption, the short version of a questionnaire investigating achievement motivation (Leistungsmotivationsinventar-kurz; Schuler & Prochaska, 2001), and German versions of the following tests: Fagerström Test for Nicotine Dependence (Bleich, Havemann-Reinecke, & Kornhuber, 2002), the Epworth Sleepiness Scale (Bloch, Schoch, Zhang, & Russi, 1999), the Karolinska Sleepiness Scale (Åkerstedt & Gillberg, 1990), the Prospective and Retrospective Memory Questionnaire (Crawford, Henry, Ward, & Blake, 2006; German translation by Kaschel, 2002), the HADS-D (Herrmann et al, 1995), the BDI-II (Hautzinger et al, 2006), the STAI (Laux et al, 1981) and a translation of the passionate love scale (Hatfield & Sprecher, 1986). For the present study, we will report the results of the BDI-II, HADS-D and STAI only.…”
Section: Methodsmentioning
confidence: 99%
“…Prior to this appointment, all patients routinely completed a set of questionnaires. Covered domains were socio-demographic data, assessment of smoking status and alcohol use, a validated German version of the Epworth sleepiness scale (ESS) (28) and the Stanford Sleep Disorders Questionnaire (29). During the appointment, a complete medical history of each patient was obtained to assess comorbidities (30) such as hypertension, coronary heart disease, diabetes, hypercholesterolemia, and current medication.…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%